A ANALISIS KEBIJAKAN ISLAM : MODEL KLASIK DAN MODERN - Irvan Irvan; Sabran; Sri Susmiati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the classical and modern models in the study of Islamic public policy and to identify their characteristics, epistemological foundations, and relevance in the context of contemporary governance. The research employs a library research method with a descriptive qualitative approach. Data sources were obtained from classical and modern literature related to fiqh siyasah, ushul fiqh, and theories of Islamic public policy. The findings indicate that the classical model of Islamic policy analysis is normative–deductive, grounded in the Qur’an and Hadith through the method of istinbath (legal derivation). In contrast, the modern model is more contextual and interdisciplinary, emphasizing the maqasid al-shariah approach and the integration of social sciences in the policy-making process. This study concludes that both models provide significant contributions to the development of public policies based on Islamic values in the modern era.